Safety assessment of poly(methylmethacrylate) nanomaterials for drug delivery: genotoxicity in mammalian cells - Bettencourt, Ana (2016)
The application of nanomaterials (NMs) as carriers for drug delivery is seen as a key factor in innovative medicine products. A major class of drug controlled release systems includes polymeric NMs, due to their unique physicochemical properties that can be manipulated using well-established techniques. Among these, polymethylmethacrylate (PMMA) is a biomedical polymer with increasing interest as a carrier system of many drugs, e.g. antibiotics, for in situ therapy. However, the same unique properties that render these NMs so valuable may underlie unforeseen toxicological adverse side effects that must be assessed prior to their application. A major concern is their long-term effects, particularly, their potential genotoxicity, given that may persist in the human body. The present work aimed at synthesizing PMMA particles for drug delivery and assessing their safety through in vitro genotoxicity testing. PMMA particles were prepared by double emulsion-solvent-evaporation methodology and the relevant properties concerning their nano-biological interactions namely, size distribution, zeta potential and hydrophobicity were measured. As part of their safety assessment the cytotoxicity (MTT test) and genotoxicity (comet and micronucleus assays) were characterized using murine L929 fibroblasts. The results showed an absence of cytotoxicity and genotoxicity. In fact, neither DNA damage nor oxidative DNA damage was detected by the comet and FPG-modified comet assay, respectively. Furthermore, no clastogenicity/aneugenicity was observed by the micronucleus assay up to 5 mg/mL (OECD-TG 487 guideline). Further studies, including in vivo mutagenicity testing, are desirable for assuring the safe use of this NM.